Melt-rock interaction near the Moho: Evidence from crystal cargo in lavas from near-ridge seamounts. (15th October 2016) - Coumans, Jason P.; Stix, John; Clague, David A.; Minarik, William G.; Layne, Graham D.
Abstract: The Taney Seamounts are a NW-SE trending linear, near mid-ocean ridge chain consisting of five volcanoes located on the Pacific plate 300 km west of San Francisco, California. Taney Seamount-A, the largest and oldest in the chain, is defined by four well-exposed calderas, which expose previously infilled lavas. The calderas can be differentiated in time by their cross-cutting relationships, creating a relative chronology. The caldera walls and intracaldera pillow mounds were sampled systematically by a remotely operated vehicle (ROV) to obtain stratigraphically-controlled samples, a unique aspect of this study. The geochemistry of the seamount varies from more differentiated to more primitive with time (6.2–8.6 wt.% MgO), suggesting that the sub-caldera reservoir is open and undergoes periodic collapse, replenishment, crystallization, and eruption. The youngest and least differentiated lavas entrained a crystal cargo of plagioclase (An80 – 90 ) with melt inclusion volatile saturation pressures indicating entrapment in the lower oceanic crust and upper mantle (6–12 km, with 45% between 8 and 10 km below the sea floor). Melt inclusions exhibit high Al2 O3, low SiO2, positive Sr and Eu anomalies and negative Zr and Nb anomalies when normalized to typical Pacific mid-ocean ridge basalt (MORB). In comparison, the host lavas exhibit positive Sr anomalies, but no concurrent Zr, and Nb anomalies. Based on thermodynamic modeling using alphaMELTS, we develop a melt-rock interaction model defined by melting and assimilation of plagioclase-rich cumulates by hot, primitive mantle-derived melts. Significantly, the variability of the negative Zr and Nb anomalies cannot be explained by either cumulate melting or AFC alone. We propose that the melt inclusions record the interaction between cumulate partial melts and the assimilating melt, demonstrating the importance of cumulate melting during the assimilation process. Later percolating melts underwent diffusive interaction with, and entrained, recrystallized plagioclase cumulates resulting in the positive Sr signal without the concurrent Eu, Zr, or Nb anomalies observed in the host lavas. These results demonstrate that melt-rock interaction at the lower crust or upper mantle is an important process at Taney Seamount-A, and potentially other magmatic systems associated with seamount chains and ridge axes.